Glycaemic control, markers of endothelial cell activation and oxidative stress in children with type 1 diabetes mellitus - Seckin, Dilara; Ilhan, Necip; Ilhan, Nevin; Ertugrul, Sabahattin (Elsevier Ireland Ltd, 2006)
Background: The aim of this study was to compare the effect of glycaemic control on oxidative stress and biochemical markers of endothelial activation in type I diabetic children. Methods: Serum total cholesterol, HDL cholesterol, VLDL cholesterol, apolipoprotein At, apolipoprotein B, HbA(1c), MDA, VEGF, NO, ICAM levels were assessed in 100 children with type I DM aged 2-17 years. Study cases were evaluated in three groups in view of their mean HbA(1c) values, as metabolically well-controlled (HbA(1c) <= 8%) and poorly controlled (HbA(1c) > 8%) patients with DM and 40 healthy children were included as normal controls. Results: Levels of MDA, NO, VEGF, ICAM, apolipoprotein A l and apolipoprotein B in metabolically poorly controlled diabetic patients were significantly higher than control group (P < 0.05). In correlation analysis of HbA(1c) to VEGF, no significant correlations were detected in metabolically well-controlled DM, but there were significant correlations between HbA(1c) and NO, MDA, ICAM levels. In correlation analysis of HbA(1c) to VEGF, NO, MDA and ICAM levels, significant corTelations were detected in poorly controlled diabetics (P < 0.05). Conclusions: In the present study, increased levels of MDA, NO, ICAM-I and VEGF levels showed that especially metabolically poorly controlled DM children are at high risk of atherosclerosis and vascular complications of DM and that there is a significant relationship between HbA(1c) and oxidative stress. It may be appropriate to evaluate levels of VEGF and sICAM-1 as well as markers of oxidative stress in addition to routine laboratory assessments in evaluation of type I DM pediatric patients. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: type 1 DM; oxidative stress; MDA; NO; VEGF; ICAM-1